2017
DOI: 10.1111/ene.13457
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of social cognition impairment in multiple sclerosis

Abstract: Background and purpose: Multiple sclerosis (MS) has been associated with deficits in social cognition. However, little is known about which domains of social cognition are predominantly affected and what other factors are associated with it. The aim was (i) to characterize social cognition deficit in a group of MS outpatients and (ii) to relate impairment in social cognition to overall cognitive status, depression and fatigue. Methods: Thirty-five MS patients (mean disease duration 12.9 years, median Expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 28 publications
5
32
1
1
Order By: Relevance
“…Contrasting this resting-state-based functional connectivity signature to those functional patterns related to other common MS symptoms (i.e., fatigue, motor/sensory function deficits, depression, anxiety) showed no overlap, lending further support to its function as distinct neural substrate. The correlation of reduced implicit ER with levels of fatigue has previously been interpreted as an indication for possible common neural networks that might underlie these symptoms (52). In general, functional connectivity maps for fatigue, motor/sensory function, and implicit ER showed very little overlap, restricted to the medial prefrontal cortex (MPFC).…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting this resting-state-based functional connectivity signature to those functional patterns related to other common MS symptoms (i.e., fatigue, motor/sensory function deficits, depression, anxiety) showed no overlap, lending further support to its function as distinct neural substrate. The correlation of reduced implicit ER with levels of fatigue has previously been interpreted as an indication for possible common neural networks that might underlie these symptoms (52). In general, functional connectivity maps for fatigue, motor/sensory function, and implicit ER showed very little overlap, restricted to the medial prefrontal cortex (MPFC).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a recent study by Neuhaus et al . (), which reported that social cognitive deficits were associated with fatigue. We hypothesized that psychosocial fatigue might be particularly relevant to social cognitive abilities, as navigating social relationships is thought to be draining for those with impairments in social cognition (Hull et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current study will examine the relationship between social cognitive abilities and fatigue. Although it has not been well‐established, there appears to be a relationship in MS between a person's social cognition and their perceived level of fatigue: a recent study found a significant relationship between social cognition (assessed by the Geneva Social Cognition Scale) and the Fatigue Scale for Motor and Cognitive Functions in individuals with MS (Neuhaus et al ., ). While this result suggests that social cognitive deficits may be related to the perception of fatigue, it is not known if they are related to all forms of fatigue.…”
Section: Introductionmentioning
confidence: 97%
“…The role played by deficits in cognitive functions on ToM impairment is another point of debate (Cabinio et al, 2015; Chalah et al, 2017; Ciampi et al, 2018; Neuhaus et al, 2018; Wade et al, 2018). This aspect is particularly interesting considering that social cognition involves specific networks that overlap and are connected with areas recruited for other cognitive functions (Henry et al, 2016).…”
Section: Introductionmentioning
confidence: 99%